2015
DOI: 10.1080/10942912.2014.966389
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Compounds in Microfiltered Pasteurized Milk Using Solid-Phase Microextraction and GC×GC-TOFMS

Abstract: Volatiles of milk were characterized by solid-phase microextraction coupled with comprehensive twodimensional gas chromatography and time-of-flight mass spectrometry. Comprehensive two-dimensional gas chromatography with time-of-flight mass spectrometry two-dimensional gas chromatography with time-of-flight mass spectrometry not only separated the 52 compounds that co-elute in conventional gas chromatography-mass spectrometry, but also identified 107 compounds that were first reported in milk. These volatiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…Similarly, Vegas and Roussis [13] reported an increase in butanoic, hexanoic, octanoic, and decanoic acids in pasteurized milk compared to raw cow milk. Acids identified in this study have previously been found in milk pasteurized by microfiltration and ultrapasteurized milk with dominance of hexanoic and octanoic acids, respectively, [18,29,44] who indicated that pasteurization with microfiltration caused a greater increase in acids than pasteurization only. Although the fat content of commercial UHT milk samples analyzed is standardized to values of ≤3% and <3.5% as UHT whole milk, the values of free fatty acids showed a wide variation from brand to brand, ranging from 25.78 to 87.96%.…”
Section: Vcssupporting
confidence: 60%
See 3 more Smart Citations
“…Similarly, Vegas and Roussis [13] reported an increase in butanoic, hexanoic, octanoic, and decanoic acids in pasteurized milk compared to raw cow milk. Acids identified in this study have previously been found in milk pasteurized by microfiltration and ultrapasteurized milk with dominance of hexanoic and octanoic acids, respectively, [18,29,44] who indicated that pasteurization with microfiltration caused a greater increase in acids than pasteurization only. Although the fat content of commercial UHT milk samples analyzed is standardized to values of ≤3% and <3.5% as UHT whole milk, the values of free fatty acids showed a wide variation from brand to brand, ranging from 25.78 to 87.96%.…”
Section: Vcssupporting
confidence: 60%
“…There is little information on oxime-methoxy phenyl. This compound has previously been found in micro-filtered pasteurized milk as dominant VOC, [18] and also in ultrapasteurized milk packaged in polyethylene terephthalate containers [29] and reconstituted milk. [44] Oximes are may be formed by reaction aldehydes or ketones with a nitrogen-containing reducing agent in a weakly acidic medium during the high heat treatment and/or homogenization since aldehydes were detected in UHT milk samples at trace levels and samples with low ketone percentages had a high level of oxime-methoxy phenyl.…”
Section: Vcsmentioning
confidence: 64%
See 2 more Smart Citations
“…It is possible that the furan 2,4-dimethylfuran (odor unknown) in the milk samples is due to the thermal degradation of certain amino acids, including serine and cysteine [52]. Further, 1,3-Bis(1,1-dimethylethyl)-benzene (odor unknown), 2,4-dimethyl-benzaldehyde (naphthyl), and tert-butylbenzene (phenolic) could have entered the milk through inhalation or ingestion, and were possibly partially degraded to phenol (phenolic) [53], however, some benzene compounds are thought to be products of the Strecker reaction [54]. For example, p-Xylene (sweet) may be present as a result of β-carotene degradation in the rumen [55], or from direct transfer from feed [56].…”
Section: Volatile Analyses (Feed Raw and Pasteurized Milk)mentioning
confidence: 99%